2020
DOI: 10.1515/revce-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Solvent impregnated resins for the treatment of aqueous solutions containing different compounds: a review

Abstract: In this review paper, a complete study and analysis of the research articles dealing with the removal of various organic and inorganic pollutants using solvent impregnated resins (SIR) is carried out. The method of impregnation, characterizations of prepared resin, and regeneration techniques of different SIRs for batch and continuous fixed bed columns are presented. The effects of different operating parameters (e.g., loading of solvent on the resin, dosage of adsorbent, initial solute concentration, pH, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 187 publications
0
3
0
Order By: Relevance
“…Therefore, an alternative approach was sought. Solvent-impregnated resins (SIRs), wherein an extractant is immobilized onto a polymeric support via hydrophobic interactions, can provide an effective means of avoiding third phase formation, and have seen applications in both sensing and separations. We thus physically immobilized receptors cis - 2 and trans - 2 onto macroporous poly­(styrene) resin Amberlite XAD4 (denoted as PS hereafter) via solvent impregnation . When 15 mg of PS was exposed to 3 mg of receptors in 5 vol % (v/v) of acetonitrile ACN/H 2 O at 60 °C for 1 h, the resins underwent a color change from opaque to amber (Figure inset).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an alternative approach was sought. Solvent-impregnated resins (SIRs), wherein an extractant is immobilized onto a polymeric support via hydrophobic interactions, can provide an effective means of avoiding third phase formation, and have seen applications in both sensing and separations. We thus physically immobilized receptors cis - 2 and trans - 2 onto macroporous poly­(styrene) resin Amberlite XAD4 (denoted as PS hereafter) via solvent impregnation . When 15 mg of PS was exposed to 3 mg of receptors in 5 vol % (v/v) of acetonitrile ACN/H 2 O at 60 °C for 1 h, the resins underwent a color change from opaque to amber (Figure inset).…”
Section: Resultsmentioning
confidence: 99%
“…For example, divalent ions are more easily adsorbed than monovalent ions. 63 Common inorganic adsorbents include alumina and zeolite, which have the characteristics of rich reserves and low price. Alumina is made by heating and dehydration of aluminum hydrate, whose properties depend on the structural state of initial hydroxide.…”
Section: Electrochemical Methodmentioning
confidence: 99%
“…The solute molecules get separated from the aqueous medium by physical adsorption and exchanging ions with the solvent or the solid material. Many studies reported that SIR is highly effective in removing different components like heavy metals, rare earths, carboxylic acids, and toxic compounds [18].…”
Section: Introductionmentioning
confidence: 99%